Ekološko usmerjena literarna veda in Prežihove samorastniške novele - Čeh Steger, Jožica (Jezik in slovstvo, 2010)
As one of the most contemporary literary science disciplines, cultural ecology is based on the hypothesis of complex analogies between natural and cultural ecosystems. At the centre of its research is the relationship between nature and culture, as it seeks to go beyond traditional thinking about their opposition. It advocates a functional model of literature, within the framework of which literature establishes itself as cultural-critical metadiscourse, imaginative antidiscourse and reintegrative interdiscourse. In Prežih's Samorastniki nature is understood in the traditional sense; however, the opposition between nature and culture as a whole does not correspond entirely to other binomials (female/male, emotion/intellect, etc.). In the article the short stories of Samorastniki are observed from the viewpoint of cultural-critical and antidiscursive function.
Keywords: Prežihov, Voranc; kulturna ekologija; ekokritike; kritični diskurz; novele